Fabrication of 4 at.% La3+ ion doped (TbxLu0.96−x)2O3 transparent ceramics by using NC-PLSH technology and characterisation of their magneto-optical properties. Issue 3 (March 2023) - Qi, Huabei; Zhou, Ding; Li, Xiaohui; Jing, Wei; Li, Weiwei; Xu, Jiayue
Abstract: Nanocrystalline powders and pressureless sintering (NC-PLSH) were used in a H2 atmosphere to fabricate 4 at.% La 3+ doped (Tbx Lu0.96−x )2 O3 magneto-optical transparent ceramics. La 3+ was utilised as a sintering aid, and Lu 3+ was used as a phase stabiliser. A component of the (Tbx Lu0.96−x La0.04 )2 O3 magneto-optical material was designed and investigated based on powder sinterability and green compact sintering. Transparent (Tbx Lu0.96−x La0.04 )2 O3 ceramics were obtained by using a one-step sintering process in H2 atmosphere, without the need for subsequent hot isostatic pressing. The in-line transmittance of the as-polished 4 at.% La 3+ :(Tb0.8 Lu0.16 )2 O3 ceramic was 79% at 1400 nm. The measured Verdet constant at wavelengths of 633 nm and 1064 nm was 354 rad/(T·m) and 100.2 rad/(T·m), respectively. The required length of the (Tb0.8 Lu0.16 La0.04 )2 O3 ceramics was 63% less than that of Tb3 Ga5 O12 ceramics.